1988
DOI: 10.1161/01.cir.78.1.41
|View full text |Cite
|
Sign up to set email alerts
|

In vivo measurement of neuronal uptake of norepinephrine in the human heart.

Abstract: Neuronal uptake (Uptake-i) of the sympathetic neurotransmitter norepinephrine from the circulation in the human heart was assessed in vivo with three techniques. 1) Cardiac removal of intravenously infused tracer-labeled norepinephrine was measured before and after Uptake-i blockade with desipramine; 2) the difference between the fractional extraction of radioactive norepinephrine and of radioactive isoproterenol, which is not a substrate for neuronal uptake, was used to estimate the removal of norepinephrine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
69
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(73 citation statements)
references
References 26 publications
4
69
0
Order By: Relevance
“…Indeed, a larger proportion of the released norepinephrine is taken up through NET in the heart compared with other organs. 19 Another possible explanation for the discordant effect of NET inhibi- tion on the heart, vasculature, and kidney is an organ-specific alteration in baroreflex regulation. In an earlier study, NET inhibition with reboxetine was associated with a shift in the baroreflex heart rate curves such that at a given blood pressure heart rate was increased.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, a larger proportion of the released norepinephrine is taken up through NET in the heart compared with other organs. 19 Another possible explanation for the discordant effect of NET inhibi- tion on the heart, vasculature, and kidney is an organ-specific alteration in baroreflex regulation. In an earlier study, NET inhibition with reboxetine was associated with a shift in the baroreflex heart rate curves such that at a given blood pressure heart rate was increased.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a larger proportion of the released norepinephrine is taken up through NET in the heart compared with other organs. 19 Another possible explanation for the discordant effect of NET inhibi- …”
mentioning
confidence: 99%
“…2,3 Peripherally, NET is perhaps most important in the heart. 4,5 In humans, approximately 92% of cardiac NE removal occurs via NET, with the remainder eliminated by extraneuronal carriers and circulatory dissipation. 6 Pharmacological blockade of NET increases extraneuronal concentrations of its substrate(s), 7 a mechanism employed in the treatment of depression and anxiety, 8,9 although autonomic side effects are common.…”
mentioning
confidence: 99%
“…The toxic levels of Fz added to the diets of poults may have resulted to a combination of myocyte injury and necrosis associated with myocardial fibrosis, which led to impaired mechanical function leading to ventricular dilation (Goldstein et al, 1998). Also addition of Fz may have led to direct toxicity or mechanical insults such as; chronic volume overload in mitral valvular regurgitation with myocyte failure and cytoskeletal uncoupling of the chambers leading to dilation (Goldstein et al, 1998). The differences observed between LVIDd and LVISd for poults fed Fz-containing diets and those in the control group are similar to that of Wu et al (2004), which reported increased left ventricular dimension for poults fed Fz-containing diets.…”
Section: Discussionmentioning
confidence: 99%